Pendampingan Peningkatan Kesadaran Diri Pasien Penyakit Tidak Menular (PTM) Melalui Program OPA-GATAN - Andriyanto, Arief; Sajidin, Muhammad (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2025)
The purpose of the community service is to assist with the collaboration program between patients, families, and health workers (OPA-GATAN) to increase self-awareness of non-communicable disease (NCD) sufferers. Hypertension, diabetes mellitus, gout, heart disease, cancer, and stroke are classified as non-communicable diseases that require treatment and management. Management of non-communicable diseases requires awareness from a sufferer and support from family and health workers in managing the disease. Disease care is packaged in the OPA-GATAN program. The method used is Community-Based Research (CBR). The community service participants were 58 diabetes mellitus sufferers and their families, and 18 local health workers. The results of the community service showed an increase in self-awareness of NCD sufferers from 12.24 (low) to 28.73 in the high awareness category. The assistance of the OPA-GATAN program in increasing the self-awareness of non-communicable disease sufferers is very effective.